Flexible Syllabus Design in EFL Curriculum A Qualitative Literature Review on Adaptation Strategies for Diverse Learners - Aulia Safitri; Anggraini, Aprillia; Rizkia, Sandrina (Institut Agama ISlam Negeri Palangka Raya, 2024)
This qualitative literature review explores the importance of flexible syllabus design in English as a Foreign Language (EFL) education. Flexibility in syllabus design is crucial to accommodate learners’ diverse needs, abilities, and contexts. The study systematically analyzes eight key academic sources discussing various syllabus design approaches; such as task-based, content-based, and negotiated syllabi—and emphasizes the significance of involving students in the planning process. Using thematic analysis, the review identifies common strategies for adapting materials, teaching methods, and assessments to be more relevant and inclusive. The main findings indicate that a flexible syllabus enhances student motivation, participation, and learning outcomes. These results suggest that flexibility in curriculum design is a key component of effective, learner-centered EFL instruction and should be promoted in policy and practice.